Improved Ability to Provide Family Hand Washing Soap Facilities In Paket Agung Village, Singaraja-Bali - Rismawan, Made; Negara, IGNM Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institute Teknologi dan Kesehatan (ITEKES) Bali, 2021)
Hand washing is a very important behavior, especially in this COVID-19 pandemic situation. This hand washing behavior needs to be instilled in all individuals starting from the family. To be able to carry out good hand washing behavior in the family, the supporting facilities and infrastructure must be prepared. One of the facilities that must be prepared is hand soap. This community service aims to improve the ability to provide family handwashing soap facilities, especially in the Agung Singaraja Village Package, Bali. The results of this Community Service (PKM) are expected to be able to increase the knowledge and behavior of the community, especially in the Package Agung Singaraja Village, Bali in carrying out hand washing behavior, especially in terms of providing family hand washing soap facilities independently. Furthermore, by implementing one of the health protocols, namely washing hands, it will be able to protect the public from the possibility of being exposed to COVID-19. The knowledge of the representatives of the community of Paket Agung Singaraja Bali about the provision of hand soap in the family has increased, this can be seen from the post-test scores which have increased. Likewise, the ability of the representatives of the community of Paket Agung Singaraja Bali in carrying out the manufacture of hand soap has increased, which can be seen from their ability to carry out the method of making hand washing soap during the red demonstration session.